Wayang Kulit Di Tangan Para Dalang Muda: Hilangnya Nilai Filosofi - Suyanto -; Aris Setiawan (Institut Seni Indonesia Denpasar, 2022)
This study aims to actualize philosophical values in shadow puppets performances for the puppeteer and the younger generation. The object of this research is a shadow puppets performance by young puppeteers in Surakarta and its surroundings. Recently, many young puppeteers have appeared arrogantly on stage, for example: standing up and trampling puppet with their feet, throwing puppet off the stage, cursing or saying rude things, exploiting sexual objects for jokes. Whether we realize it or not, one of the causes of this phenomenon is the gap in understanding the philosophical values of puppetry. Data collection methods in this study were the observation of performances and interviews, while to understand the meaning of symbols captured in shadow puppets performances, the method of understanding meaning was used. The notion of